2016
DOI: 10.1093/gastro/gow004
|View full text |Cite
|
Sign up to set email alerts
|

Association between small intestinal bacterial overgrowth and deep vein thrombosis

Abstract: Objective: Small intestinal bacterial overgrowth (SIBO) has been associated with several diseases. The association between SIBO and deep vein thrombosis (DVT) has not been investigated. This study was aimed to investigate the frequency and risk factors for the development of DVT in patients tested for SIBO.Methods: All 321 eligible patients were included from the Cleveland Clinic Gastrointestinal Motility Lab databank from January 2008 to January 2014. Patients who were evaluated with glucose hydrogen/methane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…We found that the presence of SIBO (OR 3.72; 95% CI 1.97-6.62; P < 0.001) remained associated with DVT when evaluated in the multivariate model. Consistent with our results, Fialho et al [12] suggested that SIBO was associated with DVT as an independent risk factor along with CKD and a family history of thromboembolic events in first-degree relatives.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We found that the presence of SIBO (OR 3.72; 95% CI 1.97-6.62; P < 0.001) remained associated with DVT when evaluated in the multivariate model. Consistent with our results, Fialho et al [12] suggested that SIBO was associated with DVT as an independent risk factor along with CKD and a family history of thromboembolic events in first-degree relatives.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our results, Fialho et al . suggested that SIBO was associated with DVT as an independent risk factor along with CKD and a family history of thromboembolic events in first‐degree relatives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As early as 1952, fibrin was shown to be an effective physical barrier against foreign particles [51]. DVT can be initiated by damage to the endothelial cells lining the vein wall [52] at the site of a potential infection, as well as with lipopolysaccharide endotoxemia from Gram-negative bacteremia [53], and even with colonization of the small bowel with Gram-negative bacteria [54]. Thus, thrombus represents an effective response to sepsis both because it has the potential to envelop and contain the point source of an infection, and also because it is the concentrated precipitate of filters that remove pathogens from blood [55].…”
Section: Immune Cells: Attack Then Repairmentioning
confidence: 99%